Detection of chronic wasting disease in feces and recto-anal mucosal associated lymphoid tissues with RT-QuIC in a naturally infected farmed white-tailed deer herd - Tewari, Deepanker; Fasnacht, Melinda; Ritzman, Margaret; Livengood, Julia; Bower, Jessica; Lehmkuhl, Aaron; Nichols, Tracy; Hamberg, Alex; Brightbill, Kevin; Henderson, Davin (Frontiers in Veterinary Science, 2022)
Chronic wasting disease (CWD) is an infectious prion disease affecting the cervids, including white-tailed deer (WTD) (Odocoileus virginianus). CWD is typically diagnosed postmortem in farmed cervids by immunohistochemistry (IHC). Amplification-based detection methods are newer generation tests currently being evaluated to improve the detection of prion disease. In addition to improving sensitivity, antemortem detection by amplification assays is a focus for improving disease control and management. In this study we evaluate the use of real-time quaking-induced conversion (RT-QuIC) to detect CWD in fecal and recto-anal mucosal associated lymphoid tissue (RAMALT) samples from naturally infected farmed WTD herds at post-mortem. We successfully detected the presence of CWD prions in WTD RAMALT with 100% specificity and 85.7% sensitivity (n=71) and feces with 100% specificity and 60% sensitivity (n=69) utilizing RT-QuIC on samples collected post-mortem. Seeding activity detected in RAMALT (15.3 ± 4.2% n=18) was much stronger than feces (44.4 ± 4.2% n=15), as measured by cycle threshold (Ct) and rise in relative fluorescence in samples collected from the same WTD. Prion detection in the RAMALT (94.7%) and feces (70.5%) was highest when both obex and retropharyngeal lymph nodes (RPLN) were positive for CWD via IHC. In the study group we also were able to test prion protein gene variants and associated disease susceptibility. A majority of tested WTD were of the CWD genotype (96GG) and also harbored the highest percentage of positive animals (43.7%). The second highest population of WTD were of the genotype 96GS, and had a CWD positivity rate of 37.5%. Each of these groups showed no difference in RAMALT or fecal detection of CWD.